Factors influencing early introduction of complementary feeding in children under 2 years in Limpopo province - Makhavhu, Ndiambani A.; Raliphaswa, Ndidzulafhi S.; Rangwaneni, Mphedziseni E. (Curationis (Pretoria), 2025)
Background An infant needs adequate, safe and appropriate complementary foods, with continued breastfeeding, at the age of six for survival, growth and development. However, young mothers stopped breastfeeding their children earlier than the recommended time and this often leads to the early introduction of food before the target age of 6 months. If this continues, malnutrition in children under 2 years will increase, leading to growth retardation, delayed mental development and impaired intellectual level. Objectives This article aimed to determine factors influencing early introduction of complementary feeding in children under 2 years in the selected hospitals of Vhembe District, Limpopo province. Method A qualitative approach was adopted. Purposive sampling was used to select four hospitals with high admission rates of malnutrition in the Vhembe District of the Limpopo province. Unstructured focus group discussions were conducted with 32 young mothers who were purposively sampled. Data were analysed using Tesch’s eight steps. Measures to ensure trustworthiness were employed. Ethical considerations were adhered to throughout the study. Results The study findings revealed that young mothers had different knowledge about infant feeding of children under 2 years of age because of cultural beliefs and insufficient information on appropriate food types. This may have a negative impact on the normal growth and development of children as they lack proper nutrients. Conclusion The study provided knowledge of varied beliefs and misconceptions regarding complementary feeding. Contribution This study adds information to improve young mothers’ knowledge about complementary feeding.